2016
DOI: 10.1002/cyto.a.22930
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of graft‐versus‐host‐disease in NOD scid IL‐2Rγ−/− (NSG) mice by ex vivo modulation of human CD4+ T cells

Abstract: NOD.Cg-Prkdcscid IL-2rg tm1Wjl /SzJ (NSG) mice are a valuable tool for studying Graftversus-Host-Disease (GvHD) induced by human immune cells. We used a model of acute GvHD by transfer of human peripheral blood mononuclear cells (PBMCs) into NSG mice. The severity of GvHD was reflected by weight loss and was associated with engraftment of human cells and the expansion of leukocytes, particularly granulocytes and monocytes. Pre-treatment of PBMCs with the anti-human CD4 antibody MAX.16H5 IgG1 or IgG4 attenuated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 57 publications
(91 reference statements)
1
38
0
Order By: Relevance
“…4D). Baseline liver enzyme levels in NSG mice were similar to those in BL6 mice (35). The levels of ALT in all infected mice were significantly increased over those in control animals (one-way ANOVA, P Ͻ 0.05).…”
Section: Resultssupporting
confidence: 54%
“…4D). Baseline liver enzyme levels in NSG mice were similar to those in BL6 mice (35). The levels of ALT in all infected mice were significantly increased over those in control animals (one-way ANOVA, P Ͻ 0.05).…”
Section: Resultssupporting
confidence: 54%
“…Humanized mice have been widely used to model human immune cell function in vivo (1)(2)(3)(4)(5)(6). In the Hu-PBL-SCID model, a major limitation of studying human T-cell function is the rapid development of fatal xenogeneic GVHD that not only shortens the experimental time window but also confounds the analysis of human T cell function due to the underlying ongoing acute GVHD that eventually kills the mice (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). In the present study, we have overcome this limitation by eliminating expression of murine MHC class I and II in NSG mice.…”
Section: Discussionmentioning
confidence: 99%
“…The Hu-PBL-SCID model has been used to study human infectious agents, tissue transplantation, and human T-cell immune function (2,(12)(13)(14). One of the primary uses of this model is the study of acute graft-versus-host disease (GVHD) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), a major problem in clinical hematopoietic stem cell transplantation (26). NSG mice engrafted with human PBMCs develop an acute xenogeneic GVHD-like disease upon recognition of the murine cells and tissues by mature human T cells (23).…”
mentioning
confidence: 99%
“…In many cases, the sheer numbers of RBCs in leukocyte preparations are a problem but in blood products for infusion it's the leucocytes and leucoreduction. Thus, for clinical applications it is essential to minimize their potentially adverse effects like graft versus host disease in the transfused patient. To evaluate tests quantifying blood products for residual leucocytes Zeng and colleagues conducted a multicentric study with commercial tests and found good agreement between laboratories as you can find in detail in their study report (this issue, page 420).…”
mentioning
confidence: 99%